Exosomes: The Link between GPCR Activation and Metastatic Potential? - Isola, Allison L.; Chen, Suzie (Frontiers in Genetics, 2016)
The activation of G-Protein Coupled Receptors (GPCRs) by their respective ligands initiates a cascade of multiple signaling processes within the cell, regulating growth, metabolism and other essential cellular functions. Dysregulation and aberrant expression of these GPCRs and their subsequent signaling cascades are associated with many different types of pathologies, including cancer. The main life threatening complication in patients diagnosed with cancer is the dissemination of cells from the primary tumor to distant vital organs within the body, metastasis. Communication between the primary tumor, immune system, and the site of future metastasis are some of the key events in the early stages of metastasis. It has been postulated that the communication is mediated by nanovesicles that, under non-pathological conditions, are released by normal cells to relay signals to other cells in the body. These nanovesicles are called exosomes, and are utilized by the tumor cell to influence changes within the recipient cell, such as bone marrow progenitor cells, and cells within the site of future metastatic growth, in order to prepare the site for colonization. Tumor cells have been shown to release an increased number of exosomes when compared to their normal cell counterpart. Exosome production and release are regulated by proteins involved in localization, degradation and size of the multivesicular body, whose function may be altered within cancer cells, resulting in the release of an increased number of these vesicles. This review investigates the possibility of GPCR signaling cascades acting as the upstream activator of proteins involved in exosome production and release, linking a commonly targeted trans-membrane protein class with cellular communication utilized by tumor cells in early stages of metastasis.